ENHANCING STUDENTS’ READING COMPREHENSION THROUGH KAHOOT APPLICATION - Jenny Elvinna Manurung; Berti Artika Sari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Technological innovations can be used to enhance students’ reading skills. Implementing an online tool using Kahoot could be an alternative way to improve students’ reading comprehension. The objectives of the research were to find out (1) whether there was a significant improvement in the Informatics Engineering students’ reading skills by applying Kahoot or not and (2) whether there was a significant difference in the Informatics Engineering students’ reading skills at Politeknik Sekayu between those who were taught and those who were not. The research method was a quasi-experimental design, which involved 50 Informatics Engineering students at Politeknik Sekayu as the sample selected by using purposive sampling. Reading test was used as the technique for collecting the data while paired sample t-test and independent sample t-test were used for analyzing the data. The results imply that the value of t-obtained was 4.987. The significance level was 0.000 with the degree of freedom at 48. Because the t-obtained, 4.987, was higher than t-table 1.667, and the significance level was lower than the alpha value, 0.05, therefore, there was a significant difference in Informatics Engineering students’ reading skills at Politeknik Sekayu through Kahoot between those who were taught and those who were not. Kahoot significantly improved students’ reading skills, especially in vocabulary, inference, facts and opinions, reference, scanning for detail, and main idea.